The CRY1 gene in Chlamydomonas reinhardtii: structure and use as a dominant selectable marker for nuclear transformation. - Nelson, J A (1994)
We have cloned and sequenced the CRY1 gene, encoding ribosomal protein S14 in Chlamydomonas reinhardtii, and found that it is highly similar to S14/rp59 proteins from other organisms, including mammals, Drosophila melanogaster, and Saccharomyces cerevisiae. We isolated a mutant strain resistant to the eukaryotic translational inhibitors cryptopleurine and emetine in which the resistance was due to a missense mutation (CRY1-1) in the CRY1 gene; resistance was dominant in heterozygous stable diploids. Cotransformation experiments using the CRY1-1 gene and the gene for nitrate reductase (NIT1) produced a low level of resistance to cryptopleurine and emetine. Resistance levels were increased when the CRY1-1 gene was placed under the control of a constitutive promoter from the ribulose bisphosphate carboxylase/oxygenase small subunit 2 (RBCS2) gene. We also found that the 5' untranslated region of the CRY1 gene was required for expression of the CRY1-1 transgene. Direct selection of emetine-resistant transformants was possible when transformed cells were first induced to differentiate into gametes by nitrogen starvation and then allowed to dedifferentiate back to vegetative cells before emetine selection was applied. With this transformation protocol, the RBCS2/CRY1-1 dominant selectable marker gene is a powerful tool for many molecular genetic applications in C. reinhardtii.